A Fractured Position in a Stable Partnership: Ebba Hult, Gerard De Geer, and Early Twentieth Century Swedish Geology. Issue 3 (28th July 2014) - Bergwik, Staffan
Argument This article explores the scientific partnership between geology professor Gerard De Geer and his wife Ebba Hult following their marriage in 1908. De Geer was an influential participant in Swedish academia and international geology. Hult worked as his assistant until his death in 1943. The partnership was beneficial for both spouses, in particular through the semi-private Geochronological Institute, which they controlled. The article argues that marriage was a culturally acknowledged form of collaboration in the academic community, and as such it offered Hult access to geological research. However, the paper also argues that the gendered scientific institutions produced a fractured position. Partly, Hult managed to create her own role as researcher in geochronology. As a woman and a wife, however, she never moved out of her husband's shadow. Gender is understood as a relational category: Hult was an outsider who participated partially in standardized structures which gave great power to her husband and other men. The fact that she shared this status with other women in Swedish science at the time indicates the structural nature of their position. Nevertheless, they all had individual trajectories through academia. Indeed, the study of collaborative couples illustrates the multifaceted links between individual actions and the historical context of science.